Indonesia : Staff Report for the 2004 Article IV Consultation and Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2004)
This paper reviews Indonesia's 2004 Article IV Consultation and Post-Program Monitoring Discussions. The Article IV consultation provided a timely opportunity to assess achievements under recent IMF arrangements and to take stock of remaining challenges. The discussions focused on policies to strengthen Indonesia's growth prospects. The emphasis was on identifying a set of policy actions to bolster competitiveness and growth that the authorities could implement even in an election environment. The mission recommended that the government focus on measures to address weaknesses in taxation and regulation, labor market uncertainties, and weaknesses in the legal system.